The potential influence of social networks on the adoption of breeding strategies - Pali, Pamela N.; Zaibet, L.; Mburu, S.K.; Ndiwa, Nicholas N.; Rware, H.I. (2013)
Smallholder livestock farmers face challenges such as lack of appropriate fora and networks which can motivate and influence the adoption of breeding strategies in West Africa. Efforts to ensure participation of livestock owners in breeding programs such as performance recording, the use of village herd stocks for breeding programs have been documented as has the creation of livestock producer organizations to enhance effective participation of farmers in breeding programs. The study was conducted in southern Mali where livestock such as the N’dama cattle are endemic. We explored baseline characteristics from a household and community survey to determine the potential effects of individual, household and network characteristics on the knowledge and use of livestock breeding strategies. We assume that interaction amongst stakeholders results in transfer of knowledge between stakeholders. Results from the stakeholder analysis of the types of stakeholders present at the site level were used in the Probit and Seemingly Unrelated Regression (SUR) models. Farmers’ organisations were commonly found at the village level. However, despite the presence of these organizations across sites, they do not interact with the technical organisations as often as they should hence a lower incidence of use of livestock breeding technologies across sites. Results from the models confirm the importance of networks as key determinants to improve the adoption of breeding technologies.